Hemorheological studies of chosen clinical cases - Marcinkowska-Gapińska, Anna; Kowal, Piotr (Journal of Medical Science, 2015)
Rheology – the study of the flow of matter and accompanying phenomena of real bodies deformation – in relation to blood – hemorheology. Blood viscosity – the main rheological parameter – has been studied in many research centers and among many different group of patients. The main disorders related to the hemorheological properties are: coronary insufficiency, vascular congestion, myocardial infarction, cerebral circulation disorder, Reynaud disease, ischemic limbs, diabetes, anemia, tumors. The following parameters are the main blood viscosity determinants: plasma viscosity, hematocrit, red cell deformability and erythrocytes aggregation. In hemorheological studies we used mathematical rheological models. The measurements of blood and plasma viscosity are performed by means of oscillating-rotary rheometers in order to determine the dependence of blood viscosity on the shear rate and the two components of the complex blood viscosity. Determination of blood cells aggregability and deformability is performed directly by means of aggregometers and appropiate filters and indirectly using rheological techniques with advanced mathematical models of blood viscoelasticity. Blood and plasma viscosity are subject to autoregulation mechanisms of the body. Recognition of those mechanisms may help in assessment of some diseases risk: ischemic stroke or myocardial infarction. In many cases rheological measurements may reveal the most recent phases of diseases and disorderses which enables early therapy with specimens improving the blood fluidity. For this reason rheological measurements should be applied in diagnostics and therapy. Mutual relations between the main factors determining the blood viscosity and their effect on blood flow are the main subject of current report.